Towards Using Concurrent Java API Correctly - Shuang Liu; Guangdong Bai; Jun Sun; Jin Song Dong (2016 21st International Conference on Engineering of Complex Computer Systems (ICECCS), 2016)
Concurrent Programs are hard to analyze or debug due to the complex program logic and unpredictable execution environment. In practice, ordinary programmers often adopt existing well-designed concurrency related API (e.g., those in java.util.concurrent) so as to avoid dealing with these issues. These API can however often be used incorrectly, which results in hardto-debug concurrent bugs. In this work, we propose an approach for enforcing the correct usage of concurrency-related Java API. Our idea is to annotate concurrency-related Java classes with annotations related to misuse of these API and develop lightweight type checker to detect concurrent API misuse based on the annotations. To automate this process, we need to solve two problems: (1) how do we obtain annotations of the relevant API; and (2) how do we systematically detect concurrent API misuse based on the annotations? We solve the first problem by extracting annotations from the API documentation using natural language processing techniques. We solve the second problem by implementing our type checkers in the Checker Framework to detect concurrent API misuse. We apply our approach to extract annotations for all classes in the Java standard library and use them to detect concurrent API misuse in open source projects on GitHub. We confirm that concurrent API misuse is common and often results in bugs or inefficiency.